Connecting culture and education for sustainability through transdisciplinary learning - Boyle, Evan; Mullally, Gerard; Barimo, John; Calheiros, Cristina S. C. (E- Revista de Estudos Interculturais, 2025)
As society faces increasingly critical challenges and pressures across a range of areas, third level education is under ever greater scrutiny concerning how it may provide a meaningful and significant leadership role in response. The need for education which is orientated towards navigating interrelated challenges beyond traditional disciplinary distinctions is clear, however, the ways in which this is actualised remains opaque and often restricted within embedded or possibly even disjunct cultures of learning whilst still invoking the language of “transformation”. We suggest that “culture” as a fourth pillar of sustainability, may help to enable truly novel and innovative thinking and reimagining to occur. This is needed in relation to the transformation and perhaps regeneration of educational processes and institutions and how they are understood, developed, and delivered. This is especially important with regards to the complex web of sustainability challenges underpinning the polycrisis at local, regional and global scales across all sectors of society. As an opening to a larger conversation, we propose a blended pedagogy of the transdisciplinary sustainability education praxis with transcultural education to foster global cooperation and action amidst the polycrisis.